Biodiversitas Ikan Kawasan Perairan Estuaria - Reni Sugiarti; Khairul Khairul (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the biodiversity of fish caught in the estuary waters of Sungai Bilah. The method used is explorative with determining the point of observation using purposive sampling. Fish samples were caught using splint nets. The results showed that Ambassidae and Cyprinidae dominated the relative frequency at the family level. The composition of fish species caught with the highest number was Seluang fish (109 individuals) and Sepongkah fish (107 individuals). The fish diversity index at stations 1, 2, 3 was categorized as medium and the uniformity index value was high at station 1, while at stations 2 and 3, it was classified as moderate. The dominance index values at stations 1, 2, 3 indicate that no species dominates. In conclusion, fish biodiversity in the estuary waters of Sungai Bilah is still quite good. Keywords: Fish Biodiversity, Estuary, Sungai Bilah